Distinctive distance education design models for differentiated instruction - Fuller, Richard G., 1956-; Frey, Barbara A.; Kuhne, Gary William, 1949-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2011)
"This book presents a tool to assist in the planning, conducting and evaluation of online learning, providing a way of understanding the course development and design process, drawing upon the research and theory foundations of distance education"--Provided by publisher.
1. Designing education outside of the traditional classroom -- 2. Differentiating instruction : four types of courses -- 3. Learners and learning -- 4. Designing for interaction in online courses -- 5. Social presence -- 6. Administrative issues impacting instructional design for online learning -- 7. Preactive stage : needs assessment -- 8. Preactive stage : behavioral objectives and lesson planning -- 9. Preactive stage : lesson and program evaluation -- 10. Active teaching phases : foundational pedagogies -- 11. Active teaching phases : skills based and analysis/synthesis pedagogies -- 12. Designing foundational courses -- 13. Designing skills based classes -- 14. Designing analysis/synthesis courses.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Keywords: Distance education -- Computer-assisted instruction; Instructional systems -- Design; Individualized instruction; Forms of online interaction; Social presence; Designing education outside of the traditional classroom; Differentiating instruction; Characteristics adult learners; Instructional design; Developing learner support services; Translating needs into educational language and content; Cooperative learning techniques; Asynchronous discussion boards; Electronic books